Adsorptive stripping voltammetry for simultaneous determination of hydrochlorothiazide and triamterene in hemodialysis samples using a multi-walled carbon nanotube-modified glassy carbon electrode - Hudari, Felipe Fantinato [UNESP]; Souza, João Carlos [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2018)
Hemodialysis is the most commonly used method for the treatment of chronic kidney disease. In this procedure, some patients use diuretics to control weight gain and blood pressure. In this work, a voltammetric sensor based on a glassy carbon electrode modified with carbon nanotubes (GCE/MWCNT) is described for the simultaneous determination of the diuretics hydrochlorothiazide (HCT) and triamterene (TRT). The oxidation of the diuretics on the GCE/MWCNT surface was observed at 1.01 and 1.17 V for HCT and TRT, respectively, allowing simultaneous determination, which was not possible with the unmodified glassy carbon electrode. The GCE/MWCNT electrode provided 6-fold and 10-fold gains in anode peak intensity for HCT and TRT, respectively, compared to the unmodified electrode. After optimization of the conditions (pH, accumulation time, and accumulation potential), analytical curves were constructed for the analytes in the range from 1.0 × 10−7 to 2.0 × 10−5 mol L−1. The detection limits for HCT and TRT were 2.8 × 10−8 and 2.9 × 10−8 mol L−1, respectively. A high performance liquid chromatography method with diode array detection was also developed for the determination of HCT and TRT in hemodialysis samples, for comparison with the electroanalytical method.
Keywords: Diuretic; Modified electrode; Sensor; Stripping voltammetry; Voltammetric method